Supplementing Ruminally Protected Lysine, Methionine, or Combination Improved Milk Production in Transition Dairy Cows - Elsaadawy, Samy A.; Wu, Zaohai; Wang, Han; Hanigan, Mark D.; Bu, Dengpan (Frontiers in Veterinary Science, 2022)
The objectives of this study were to evaluate the effects of dietary supplementation of ruminally protected lysine (RPL), or methionine (RPM), and their combination (RPML) on the production efficiency of transition cows. A total of 120 pre-partum multiparous Holstein cows were assigned to four treatments based on previous lactation milk production, days (d) of pregnancy, lactation, and body condition score (BCS). Cows were fed a basal diet [pre-calving: 1.53 Mcal/kg dry matter (DM) and post-calving: 1.70 Mcal/kg DM] with or without supplemental ruminally protected amino acids (RPAA). Treatments were the basal diets without supplemental amino acids (CONTROL, n = 30), with supplemental methionine (RPM, pre-calving at 0.16% of DM and post-calving at 0.12% of DM, n = 30), with supplemental lysine (RPL, pre-calving at 0.33% of DM and post-calving at 0.24% DM, n = 30), and the combination (RPML, pre-calving at 0.16% RPM + 0.33% RPL of DM and post-calving at 0.12% RPM + 0.24 % RPL DM, n = 30). The dietary content of lysine was balanced to be within 6.157.2% metabolizable protein (MP)–lysine and that of methionine was balanced within 2.1–2.35% MP-methionine. Dry matter intake (DMI) was measured daily. Milk samples were taken on d 7, 14, and 21 days relative to calving (DRC), and milk yields were measured daily. Blood samples were taken on d −21, −14, −7 before expected calving and d 0, 7, 14, and 21 DRC. Data were analyzed using SAS software. There were significant Trt × time interactions (P < 0.01) for DMI pre- and post-calving period. The CON cows had lower DMI than RPM, RPL, and RPML, both pre-calving (P < 0.01) and post-calving periods (P < 0.01). Energy-corrected milk (P < 0.01), milk fat (P < 0.01), protein (P = 0.02), and lactose (P < 0.01) percentage levels were greater for RPM, RPL, and RPML cows compared to CON. Supplementing RPAA assisted in maintaining BCS post-calving than CON (P < 0.01). Blood concentrations of β-hydroxybutyrate decreased with RPM or RPL or the combination pre-calving (P < 0.01) and tended to decrease post-calving (P = 0.10). These results demonstrated that feeding RPL and RPM improved DMI and milk production efficiency, maintained BCS, and reduced β-hydroxybutyrate concentrations of transition cows.